2018
DOI: 10.1111/lam.13051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of next-generation droplet digital PCR with quantitative PCR for enumeration of Naegleria fowleri in environmental water and clinical samples

Abstract: This study explored the application of ddPCR and qPCR methods in identifying Naegleria fowleri from both clinical and environmental water samples. Strong agreement between ddPCR and qPCR methods over clinical DNA samples was observed. Naegleria fowleri was present in surface water samples from Lake Pontchartrain during our study period. The ability of N. fowleri to survive in brackish water is therefore a potential risk factor for people who engage in water-related recreational activities. The ddPCR performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…Some of this may relate to the issue of viability discussed in the next section. For example, Xue et al 33 found close correspondence between qPCR and dPCR measurements of Naegleria fowleri in spiked water. In contrast, Ricchi et al 34 analyzed water samples spiked with three strains each of three bacteria using plate count, qPCR, and dPCR (on two instruments) as shown in Figure 2.…”
Section: ■ Information Needed For Qmramentioning
confidence: 97%
See 1 more Smart Citation
“…Some of this may relate to the issue of viability discussed in the next section. For example, Xue et al 33 found close correspondence between qPCR and dPCR measurements of Naegleria fowleri in spiked water. In contrast, Ricchi et al 34 analyzed water samples spiked with three strains each of three bacteria using plate count, qPCR, and dPCR (on two instruments) as shown in Figure 2.…”
Section: ■ Information Needed For Qmramentioning
confidence: 97%
“…Some of this may relate to the issue of viability discussed in the next section. For example, Xue et al found close correspondence between qPCR and dPCR measurements of Naegleria fowleri in spiked water. In contrast, Ricchi et al .…”
Section: Information Needed For Qmramentioning
confidence: 97%
“…High-throughput qPCR using microfluidic technology is demonstrated as a direct multi-pathogen detection approach for environmental water samples. This technology makes use of microfluidic chips, which allow for high-throughput measurement of large sample quantities for a variety of enteric viruses and other pathogens [53,54].…”
Section: Culture Versus Molecular Detectionmentioning
confidence: 99%
“…Droplet digital PCR (ddPCR) is also shown to have improved performance in the presence of inhibitory compounds as compared to qPCR [54,55]. ddPCR performs better because it is an end-point positive/negative detection combined with Poisson statistics for quantification, so it has higher accuracy and precision against PCR inhibition.…”
Section: Culture Versus Molecular Detectionmentioning
confidence: 99%
“…dPCR offers lower impacts from sample inhibitors, independence from calibration curves, high levels of precision (Pavsic et al, 2017) and may improve sensitivity (e.g. Xue et al, 2018). Finally, we compared both platforms using samples collected from an active farm with a history of high K. thyrsites impact.…”
Section: Introductionmentioning
confidence: 99%